Enhancement of Potential Field Source Boundaries Using an Improved Logistic Filter - Pham, Luan Thanh; Van Vu, Tich; Le Thi, Sang; Trinh, Phuong Thi (Pure and applied geophysics, 2020)
Detection of source horizontal boundaries is a common feature in the interpretation of magnetic and gravity data. A wide range of derivative- and phase-based methods are available to solve this problem. Here, we compare the effectiveness of the commonly used methods, and introduce a method based on the logistic function and the horizontal gradient amplitude, which shows improved performance as a boundary detection filter. The effectiveness of the proposed filter is demonstrated by evaluating synthetic examples and a real example from the Central Puget Lowland (United States). The main advantage of this method is that it provides high-resolution results, and can avoid producing spurious boundaries in the output maps.